Analysis and verification of physical properties of an AISI 4140 steel by Vickers indentation analysis according to the presence of residual stresses - Jung, Changho; Lee, Moon G.; Jeon, Yongho (Archives of Metallurgy and Materials, 2019)
Residual stress has a great influence on the metal, but it is difficult to measure at small area using a general method. Residual stress calculations using the Vickers indentation can solve this problem. In this paper, a numerical simulation has been made for the residual stress measurement method of metal material deformed by high-speed impact. Then, the stress-strain curve at the high-speed deformation was confirmed through actual experiments, and the residual stresses generated thereafter were calculated by the Vickers indenter method. A Vickers indentation analysis under the same conditions was performed at the position where a residual stress of about 169.39 MPa was generated. Experiments were carried out and high speed impact was applied to the specimen to generate residual stress. The obtained results indicate that it is possible to identify residual stresses in various metals with various shapes through Vickers indentation measurements, and to use them for process and quality control.
Keywords: Actual experiments; Analysis and verifications; FEM analysis; High speed impact; High-speed deformation; Stress calculations; Vickers indentation; Vickers indenters; FEM Analysis; Material Property; Residual stress; Surface Treatment; Vickers indentation